2017
DOI: 10.1002/macp.201700236
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable Promotion Effect of Sulfation over the SiO2‐Supported Vanadium‐Oxide‐Based Catalysts for UHMWPE

Abstract: The effects of sulfation on VOx/SiO2–MOy (M = Al, Zr, or Ti) are systemically studied for the synthesis of ultrahigh molecular weight polyethylene (UHMWPE), showing that the activity remains stable under the investigated polymerization temperature (Tp) from 70 to 90 °C, and is almost doubled after sulfation. According to the results of NH3–TPD, pyridine‐adsorption‐fourier transform infrared spectroscopy (FTIR) and X‐ray photoelectron spectroscopy (XPS), the enhancement effect in activity is likely related to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…In our prior research, we successfully synthesized an array of high-performance bimodal PE in reactor alloys using custom-designed catalysts. [43][44][45][46][47][48] Subsequently, we created a series of HDPE/UHMWPE blends through solution blending, characterizing their exceptional mechanical properties. 49 Our findings revealed that incorporating UHMWPE increased the blend's crystallization rate, while elevating the ultrasonic intensity led to more stable crystal nucleus structures and thicker crystal layers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our prior research, we successfully synthesized an array of high-performance bimodal PE in reactor alloys using custom-designed catalysts. [43][44][45][46][47][48] Subsequently, we created a series of HDPE/UHMWPE blends through solution blending, characterizing their exceptional mechanical properties. 49 Our findings revealed that incorporating UHMWPE increased the blend's crystallization rate, while elevating the ultrasonic intensity led to more stable crystal nucleus structures and thicker crystal layers.…”
Section: Introductionmentioning
confidence: 99%
“…In our prior research, we successfully synthesized an array of high‐performance bimodal PE in reactor alloys using custom‐designed catalysts 43–48 . Subsequently, we created a series of HDPE/UHMWPE blends through solution blending, characterizing their exceptional mechanical properties 49 .…”
Section: Introductionmentioning
confidence: 99%